2008
DOI: 10.1007/s00423-007-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and the risk of pancreatic cancer: a review and meta-analysis

Abstract: Based on estimates from four continents, smoking cigarettes causes a 75% increase in the risk of pancreatic cancer compared to non-smokers, and the risk persists for a minimum of 10 years after smoking cessation. This implies that in a population where the prevalence of smoking is 30%, the population's attributable risk (the proportion of pancreatic cancer explained by smoking) is estimated to be 20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
324
6
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 478 publications
(368 citation statements)
references
References 82 publications
23
324
6
15
Order By: Relevance
“…Heavy alcohol consumption can increase the risk of pancreatic cancer (Lucenteforte et al, 2012), as well as smoking (Iodice et al, 2008), sucrose-intake6 (Aune et al, 2012), processed meat consumption (Larsson et al, 2012) and high body mass index (Li et al, 2010), while folate intake (Bao et al, 2011) and coffee consumption (Dong et al, 2011) are not appreciably related to pancreatic cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy alcohol consumption can increase the risk of pancreatic cancer (Lucenteforte et al, 2012), as well as smoking (Iodice et al, 2008), sucrose-intake6 (Aune et al, 2012), processed meat consumption (Larsson et al, 2012) and high body mass index (Li et al, 2010), while folate intake (Bao et al, 2011) and coffee consumption (Dong et al, 2011) are not appreciably related to pancreatic cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of pancreatic cancer is raised by 75 % as compared to nonsmokers, risk persisting minimum of 10 years after cessation of smoking when the risk gradually diminishes to the baseline [17]. Another study that included nearly 13,000 patients with pancreatic cancer showed that current smokers had an odds ratio of 2.2, compared with never smokers, and the odds ratio was 1.2 for ex-smokers.…”
Section: Smokingmentioning
confidence: 99%
“…Smoking is the single biggest cause of cancer worldwide and is responsible for around a third of all cancer deaths (IARC, 2004;Sasco et al, 2004). Smoking significantly increases the risk of lung cancer, mouth cancer, bladder cancer, kidney cancer, oesophageal cancer, pancreatic cancer and stomach cancer (Brennan et al, 2000;Iodice et al, 2008;Johnson, 2001;Parkin et al, 2011). Alcohol consumption can significantly increase the risk of mouth cancer, liver cancer, oesophageal cancer, breast cancer, laryngeal cancer and colorectal cancer (Bagnardi et al, 2001;Blot, 1992;Key et al, 2006).…”
Section: Holly Blake and Rebekah E Tennyson 4 Lifestyle Factors And mentioning
confidence: 99%